2015
DOI: 10.1371/journal.pone.0126657
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of the AP2/ERF Transcription Factors Family and the Expression Patterns of DREB Genes in Moso Bamboo (Phyllostachys edulis)

et al.

Abstract: The AP2/ERF transcription factor family, one of the largest families unique to plants, performs a significant role in terms of regulation of growth and development, and responses to biotic and abiotic stresses. Moso bamboo (Phyllostachys edulis) is a fast-growing non-timber forest species with the highest ecological, economic and social values of all bamboos in Asia. The draft genome of moso bamboo and the available genomes of other plants provide great opportunities to research global information on the AP2/E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(71 citation statements)
references
References 94 publications
3
68
0
Order By: Relevance
“…Peng et al (2013) reported a putative recent whole genome duplication at 7-12 MYA based on analyzing whole genome duplication events of P. edulis . Wu et al (2015) found that P. edulis genome underwent a large-scale event around 15 MYA by genome-wide analysis of AP2/ERF transcription factors. Our result is similar to these reports and supported that the expansion of PeTIFYs occurred along with the genome duplication event.…”
Section: Resultsmentioning
confidence: 99%
“…Peng et al (2013) reported a putative recent whole genome duplication at 7-12 MYA based on analyzing whole genome duplication events of P. edulis . Wu et al (2015) found that P. edulis genome underwent a large-scale event around 15 MYA by genome-wide analysis of AP2/ERF transcription factors. Our result is similar to these reports and supported that the expansion of PeTIFYs occurred along with the genome duplication event.…”
Section: Resultsmentioning
confidence: 99%
“…There are two classes of DREB transcription factors, DREB1 and DREB2. DREB1 involved in signal transduction pathways under cold stress, while DREB2 is induced under dehydration [7,8,20]. However, DREB1 and DREB2 genes have sequence similarity at AP2 domain and bind to the same DRE sequence.…”
Section: Resultsmentioning
confidence: 99%
“…Based on functional validation those genes are grouped into several classes such as transcription, osmolyte biosynthesis, signal transduction, hormone metabolism, and macromolecule protection [5,6]. Among those genes, DREB (dehydration responsive element binding) gene is a well˗studied group of genes in abiotic stress [7,8].DREB has an important role in stress signal transduction since it activates expression of many stress˗inducible target genes [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, AT5G43410 encodes members which bind to GCC elements at the promoter of their target genes and are induced by pathogens. The AP2/ERF family is one of the largest of TFs family that are involved in plant development and response to abiotic stresses as well as pathogen attack via ethylene signaling pathway (Wu et al, 2015;Guo and Ecker, 2002). They act as a trans-acting factor interact with drought-responsive elements triggering downstream regulation events to improve stress tolerance in plants.…”
Section: Analysis Of Cis-regulatory Elements In Putative Target Genesmentioning
confidence: 99%